WOMEN'S LEADERSHIP IN AISYIYAH ORGANIZATIONS: (Study on Implementation and Challenges at The Regional Level) - Siwiyanti, Leonita; Komariah, Kokom; Ramdan, Asep Muhamad (Islamic Management: Jurnal Manajemen Pendidikan Islam, 2025)
This study analyzes the implementation and challenges of women's leadership in Aisyiyah organizations at the regional level, especially in Sukabumi Regency. The background of this study is based on the importance of women's leadership in religious organizations that still face gender stereotypes. Using a quantitative-descriptive approach, data were collected through questionnaires and interviews with 20 leaders and 100 members of Aisyiyah. The results of the study show that women's leadership is considered adequate and has a positive impact on the success of the program. However, challenges such as limited resources and cultural barriers are still felt. Leaders use collaborative strategies, training, and participatory approaches to address them. These findings confirm the importance of leadership training and structural support to optimize women's contributions in religious organizations.